2022
DOI: 10.1108/srj-01-2022-0040
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between employees’ attributions of corporate social responsibility, organisational justice and turnover intention: evidence from a post-Soviet country

Abstract: Purpose Corporate social responsibility (CSR) does not always create added value. Depending on the employee attributions to a socially responsible organisation, it can lead even to negative behaviour. One of the dangers discussed in this article is the employees’ turnover intentions. To analyse the relationship in-depth, it is important to identify phenomena that could be significant to the strength of the relationship between the employees’ attributions to socially responsible organisations and the turnover i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In a survey of 466 employees in large Chinese companies, Yang Cheng found that employees' cynical emotions towards CSR increased their distrust in the organization, leading to an increased intention to resign (Cheng et al, 2022). Zeimiene's study demonstrated that in organizations with responsibility-oriented attributes, employees are less likely to have intentions to resign and perceive the organization as fair (Zeimiene et al, 2023).…”
Section: Previous Studies On Corporate Social Responsibility (Csr)mentioning
confidence: 99%
“…In a survey of 466 employees in large Chinese companies, Yang Cheng found that employees' cynical emotions towards CSR increased their distrust in the organization, leading to an increased intention to resign (Cheng et al, 2022). Zeimiene's study demonstrated that in organizations with responsibility-oriented attributes, employees are less likely to have intentions to resign and perceive the organization as fair (Zeimiene et al, 2023).…”
Section: Previous Studies On Corporate Social Responsibility (Csr)mentioning
confidence: 99%